Overexpression of Cyclin D3 Improves Decidualization Defects in Hoxa-10(−/−) Mice - Sroga, Julie M. (Endocrine Society, 2012)
Uterine decidualization, a crucial process for implantation, is a tightly regulated process encompassing proliferation, differentiation, and polyploidization of uterine stromal cells. Hoxa (Homeobox A)-10, a homeobox transcription factor, is highly expressed in decidualizing stromal cells. Targeted gene deletion experiments have demonstrated marked infertility resulting from severely compromised decidualization in Hoxa-10(−/−) mice. However, the underlying mechanism by which Hoxa-10 regulates stromal cell differentiation remains poorly understood. Cyclin D3, a G(1) phase cell-cycle regulatory protein involved in stromal cell proliferation and decidualization, is significantly reduced in Hoxa-10(−/−) mice. The expression of cyclin D3 in the pregnant mouse uterus parallels stromal cell decidualization. Here, we show that adenovirus-driven cyclin D3 replacement in Hoxa-10(−/−) mice improves stromal cell decidualization. To address our question of whether cyclin D3 replacement in Hoxa-10(−/−) mice can improve decidualization, both in vitro and in vivo studies were completed after the addition of cyclin D3 or empty (control) viral vectors. Immunostaining demonstrated increased proliferation and decidualization in both in vitro and in vivo studies, and in situ hybridization confirmed increased expression of decidualization markers in vivo. Placentation was demonstrated as well in vivo in the cyclin D3-replaced animals. However, fertility was not restored in Hoxa-10(−/−) mice after d 10 of pregnancy. Finally, we identified several downstream targets of cyclin D3 during decidualization in vitro via proteomics experiments, and these were confirmed using in situ hybridization in vivo. Collectively, these results demonstrate that cyclin D3 expression influences a host of genes involved in decidualization and can improve decidualization in Hoxa-10(−/−) mice.